Forbidden Love, Meat and Cannibalism: An Analysis of Bhaskar Hazarika’s Aamis (Ravening) - Sarmah, Riswita (SARE: Southeast Asian Review of English, 2023)
Abstract The paper attempts to explore Aamis (Ravening) (2019), an Assamese film from India, written and directed by Bhaskar Hazarika. The film chronicles a story of passion between Nirmali, a married woman and Sumon, a young researcher. Sumon, a meat connoisseur, studying the meat eating habits of different communities serve as a metafictional strategy of the film. Meat becomes a mode of showcasing liminality and the body politic. The two create a carnivalesque world for themselves, where meat becomes a medium of expressing their unprofessed desire. With the turn of events Sumon makes Nirmali taste his own flesh, camouflaging it as an exotic meat. Resulting in Nirmali’s extreme yearning for human flesh. Nirmali undergoes a process of ’unfinalizability’, revealing a side to herself that she had never known. Aamis through its surrealistic portrayal of cannibalism brings forth the grotesque and the macabre. Nirmali’s desire for human meat turns her into a monstrous ’other’. Sumon and Nirmali become figures of ’homo-sacer’, beyond the control of the state. In the conclusive scene, for the first time Nirmali touches Sumon, in public with faces covered by cloth. The markers of identity become ineffectual by then. Almost indifferent to the world around them, they stand as lovers hand in hand who had tasted, that which is "forbidden".